PENERAPAN MODEL PEMBELAJARAN STAD (STUDENT TEAMS-ACHIEVEMENT DIVISION) TERHADAP HASIL BELAJAR KETEPATANÂ SERVICE BAWAH BOLAVOLI - ADITAMA, ZAINAL (Jurnal Pendidikan Olahraga dan Kesehatan, 2014)
Abstract Volleyball become popular sport branch on Indonesia, all society stratum can play and learn it. For they who pursue achievement from this sport branch or just as an hobby for they as an amateurs. With simple rules of game, volleyball can be taught on elementary school children aged, junior high school to senior high school. Basic techniques that taught on elementary school and junior high school level can be increased on teenager age on highschool level. E.g. on performing underhand service basic technique, which previously only able to executed or through the net, further learning will increase its accuracy to certain target field that difficult to reach by opponent. Problem that appear during learning at school is one physical education teacher must be able to give maximal learning to every students, whereas certainly become a problem when the amount of student is quite a lot with different character and ability as well as limited learning time. Therefore, researcher execute research with STAD learning model to one of schools on Madiun, exactly on SMA Negeri 1 of Madiun City. SMA Negeri 1 Madiun considered to be appropriated since its one of the favourite public highschools, not just from the academic, but also from its sports achievement that deserved to considered at Madiun City. This research expected able to improve learning quality to be spread evenly on SMA Negeri 1 Madiun.     Research which conducted applying AAHPER underhand service accuracy test norm with pseudo experiment research and one group pretest - posttest research design. Sample collecting technique using purposive sample technique based on the recommendation from physical education teacher, banely Class XI IPS 1 with the amount of 36 students. All student of Class XI IPS 1 that amounted of 36 students will be divided to become 8 learning groups hetergenously to receive treatment in every meeting. Based on the research result, its obtained data with significant improvement for volleyball underhand service accuracy learning result as big as 63.93%.       Keywords: STAD learning model, Volleyball underhand service.